Design and building CNC engraving router machine using Arduino Uno with GRBL control system - Irwansyah, Defi; Asnawi, Asnawi; Ula, Mutammimul; Sahputra, Ilham; Sahbana, Bagas Nur; Arrahman, Fadly (Edelweiss Applied Science and Technology, 2024)
Computer Numerical Control Machines are one of the advances in automatically operated machining technology that can meet the need for complex and high-precision products. CNC machine parts generally have a mechanical and electrical system, also called a machine controller, that uses a Human Machine Interface at a high price. One of the software used to control the CNC machine is Arduino Uno, a PC-based GRBL System with a low price and the same function. This software is not far from the advantages of the HMI panel. Operating the machine with this software is also not that difficult. In this research, we intend to make a CNC machine using the Arduino Uno control system and software with a PC-based GRBL System, making it easier for operators to operate it. The results of the research that has been carried out show that the CNC has a size of 800x600x50mm with a system that is operated well and precisely